Implementation of Guess The Picture Learning Strategy in Al-Muhadasah Class 2 MTS Lessons - Agus Budiman; Muhammad Sholahuddin (al-Afkar, Journal For Islamic Studies, 2025)
Learning Arabic requires an understanding of four skills: listening, speaking, reading, and writing. Pondok Modern Darussalam Gontor is an educational institution with Kulliyyatul Mu'allimin Al-Islamiyah curriculum that teaches Arabic and English. Researchers found that the difficulties of class students are expected to be achieved. How to teach a good teacher is the key and prerequisite for students to be able to learn well.  Teachers are expected to be able to choose the right way of teaching so that they can create a conducive learning environment system and activate students, one of the right learning strategies applied is a learning strategy, namely the Guess The Picture Strategy in Arabic Language Learning at MTSN 2 Ponorogo.